Indigenous Knowledge and Food Security of Tunggu Tubang Community in Semende, South Sumatra - Meilinda; Yenny Anwar; Retno Cahya Mukti; Windi Indah Fajar Ningsih; Delima Engga Maretha (Postgraduate, University of Mataram, 2023)
This research aims to identify and document the local food security system in the Semende traditional community based on tunggu tubang indigenous knowledge. The study was conducted in 3 districts of Muara Enim, South Sumatra, involving 81 people from 5 villages practicing the tunggu tubang custom. Using a mixed method, the research took place from July to August 2023.The findings revealed that while tunggu tubang adherents still inherit rice fields and agricultural land, some no longer own rice fields. Inheriting rice fields has led to sufficient food availability but does not guarantee good food security. 50.6% of respondents experienced mild food insecurity due to the traditional sandwich generation where they have to support their parents and closest family. Despite this, most children (56.6%) showed good nutritional status. This research identifies and documents the local food security system in the Semende traditional community. It reveals the importance of tunggu tubang in maintaining food availability but acknowledges the challenges in achieving food security. The findings provide valuable insights for developing educational initiatives to address climate change and food security